Staff apraisal report: Judicial reform project: Ecuador - (:unkn) unknown (My University, 2016)
A judicial sector review was completed by the World Bank in order to assess the current state of the judicial system and provide recommendations for reform which were endorsed by the Supreme Court as well as the Executive Branch. The proposed project incorporates the main weaknesses identified in the sector review. To summarize, the judicial sector has four major weakness which contribute to the deficiencies of the judicial process: lack of administrative organization by the courts including the lack of appropriate management techniques, professional staff and administrative procedures, an inadequate judicial infrastructure, inadequate availability of alternative dispute resolution and limited access to justice for the poor and lack of legal training available to lawyers, judges and students.